Evaluation of dimethylsulfoxide and Aloe vera as penetration enhancers for cutaneous application of lidocaine - Mangesh A. Bhutkar; Somnath D Bhinge; Dheeraj S Randive; Omprasad Nayakal; Prajakta Patil
ABSTRACT Objective: The objective of the present work was to compare and verify efficacy of Aloe vera (1 to 3 %) with dimethyl sulfoxide (1 to 3 %) for its penetration enhancing property for topical delivery of lidocaine. Method: Carbopol 934 was used as gelling agent for preparation of lidocaine gel formulations containing or not dimetilsulfoxido or Aloe vera (1%, 2% and 3%). Gels were evaluated for physical appearance, rheological behavior, drug content, drug release and stability. Results: It was inferred from result that obtained gel formulation were good in appearance, homogeneity and consistency. In vitro drug release profiles showed that concentrations of Aloe vera gel increased in formulations, the drug release rate increased substantially. It was observed that F6 formulation which comprised of 3% Aloe vera as permeation enhancer exhibited 79.18 % of drug release. Similarly, for formulation F3 which comprised of 3% dimetilsulfoxido as permeation enhancer the drug release was found to be 84.52%. Use of Aloe vera may prove to be beneficial as compared to synthetic permeation enhancers. Conclusion: Based on results of the study it was concluded that the topical gel of lidocaine prepared along with Carbopol 934 by using Aloe vera as a natural penetration enhancer at a concentration of 3% can be used to enhance the penetration for lidocain across the skin.